Perturbations in eIF3 subunit stoichiometry alter expression of ribosomal proteins and key components of the MAPK signaling pathways - Herrmannová, Anna; Jelínek, Jan; Pospíšilová, Klára; Kerényi, Farkas; Vomastek, Tomáš; Watt, Kathleen; Brábek, Jan; Mohammad, Mahabub Pasha; Wagner, Susan; Topisirovic, Ivan; Valášek, Leoš Shivaya (eLife, 2024)
Protein synthesis plays a major role in homeostasis and when dysregulated leads to various pathologies including cancer. To this end, imbalanced expression of eukaryotic translation initiation factors (eIFs) is not only a consequence but also a driver of neoplastic growth. eIF3 is the largest, multi-subunit translation initiation complex with a modular assembly, where aberrant expression of one subunit generates only partially functional subcomplexes. To comprehensively study the effects of eIF3 remodeling, we contrasted the impact of eIF3d, eIF3e or eIF3h depletion on the translatome of HeLa cells using Ribo-seq. Depletion of eIF3d or eIF3e, but not eIF3h reduced the levels of multiple components of the MAPK signaling pathways. Surprisingly, however, depletion of all three eIF3 subunits increased MAPK/ERK pathway activity. Depletion of eIF3e and partially eIF3d also increased translation of TOP mRNAs that encode mainly ribosomal proteins and other components of the translational machinery. Moreover, alterations in eIF3 subunit stoichiometry were often associated with changes in translation of mRNAs containing short uORFs, as in the case of the proto-oncogene MDM2 and the transcription factor ATF4. Collectively, perturbations in eIF3 subunit stoichiometry exert specific effect on the translatome comprising signaling and stress-related transcripts with complex 5' UTRs that are implicated in homeostatic adaptation to stress and cancer.
Keywords: ribosome; Ribosomal Proteins; Protein Biosynthesis; proteosyntéza; translational control; MAP kinasový signální systém; HeLa buňky; ribosomal proteins; human; MAP Kinase Signaling System; ribozomální proteiny; eukaryotický iniciační faktor 3; lidé; HeLa Cells; Humans; translation; Eukaryotic Initiation Factor-3; Proto-Oncogene Mas; genomics; MAPK pathway; genetics; eIF3; protoonkogen Mas